Quantifying the Elasticity Properties of the Median Nerve during the Upper Limb Neurodynamic Test 1. (20th March 2022) - Lin, Ming; Chen, Yaodong; Deng, Weixin; Liang, Hongying; Yu, Suiqing; Zhang, Zhijie; Liu, Chunlong
Abstract : Background . The upper limb neurodynamic test 1 (ULNT1) consists of a series of movements that are thought to detect an increase in neuromechanical sensitivity. In vivo, no trail was made to quantify the association between the nerve elasticity and different limb postures during ULNT1. Objectives . (1) To investigate the relationship between nerve elasticity and limb postures during ULNT1 and (2) to investigate the intra- and interoperator reliabilities of shear wave elastography (SWE) in quantifying the elasticity of median nerve. Methods . Twenty healthy subjects (mean age: 19.9 ± 1.4 years old) participated in this study. The median nerve was imaged during elbow extension in the following postures: (1) with neutral posture, (2) with wrist extension (WE), (3) with contralateral cervical flexion (CCF), and (4) with both WE and CCF. The intra- and interoperator reliabilities measured by two operators at NP and CCF+WE and intraclass correlation coefficients (ICCs) were calculated. Results. The intraoperator (ICC = 0.72 – 0.75 ) and interoperator (ICC = 0.89 – 0.94 ) reliabilities for measuring the elasticity of the median nerve ranged from good to excellent. The mean shear modulus of the median nerve increased by 53.68% from NP to WE+CCF. Conclusion. SWE is a reliable tool to quantify the elasticity of the median nerve. There was acute modulation in the elasticity of the median nerve during the ULNT1 when healthy participants reported substantial discomfort. Further studies need to focus on the elasticity properties of the median nerve in patients with peripheral neuropathic pain.